Should tumor size concern us in nonmetastatic colon adenocarcinoma? - Uzunoğlu, Hakan; Kaya, Selçuk (Journal of Surgery and Medicine, 2021)
Background/Aim: Limited data are evaluating whether tumor diameter and the prognostic criteria are directly related to each other in colon adenocarcinoma cases. This study aimed to evaluate the relationship between tumor diameter and prognostic factors in non-metastatic colon adenocarcinomas. Methods: Two hundred and sixty patients operated on due to colon adenocarcinoma and followed up in the General Surgery Department of our hospital between January 2015-December 2020 were included in this retrospective cohort study. The relationship between tumor size and lymphovascular invasion, perineural invasion, lymph node metastasis, and N-ratio was evaluated according to localization. Results: The mean age of the patients was 63.3 (12.3) (min.-max.: 24-94) years. One hundred and sixty (61.5%) patients were male. The tumor was in the right colon (proximal to the splenic flexure) in 31%, and lymph node metastasis was detected in 43.5%. The number of metastatic lymph nodes and N-ratio values were similar according to tumor diameter (P>0.05 for each). Tumor diameter, the number of metastatic lymph nodes, and N-ratio values were not significantly correlated in the groups made according to localization (P>0.05 for each). The median tumor diameter was similar in patients with right colon and left colon cancer with and without lymph node metastasis. Likewise, no significant difference was found between the N stages in terms of median tumor diameter (P>0.05 for each). Conclusion: Our findings show that tumor diameter is not directly related to lymph node metastasis or N-ratio in non-metastatic colon adenocarcinomas and that it does not provide reliable information about lymph node metastasis.